Life Cycle Assessment of Geothermal Power Technologies for Indonesia’s Energy Transition: A Review of Environmental Hotspots and Optimization Strategies - Rajagukguk, Vania Larissa; Dahlan, Astryd Viandila (International Journal Labs, 2025)
Indonesia has set a target to achieve Net Zero Emissions (NZE) by 2060 and a 52% renewable energy share by 2030. Geothermal energy, with 29.5 GW potential, is critical, yet environmental performance of technologies remains poorly characterized, hindering sustainable decisions. This systematic review analyzes life cycle assessment (LCA) studies on binary, flash, and dry steam geothermal technologies. Scopus and Google Scholar searches using keywords